Concise gene signature for point‐of‐care classification of tuberculosis. Issue 2 (18th December 2015) - Maertzdorf, Jeroen; McEwen, Gayle; Weiner, January; Tian, Song; Lader, Eric; Schriek, Ulrich; Mayanja‐Kizza, Harriet; Ota, Martin; Kenneth, John; Kaufmann, Stefan HE
Abstract: There is an urgent need for new tools to combat the ongoing tuberculosis (TB) pandemic. Gene expression profiles based on blood signatures have proved useful in identifying genes that enable classification of TB patients, but have thus far been complex. Using real‐time PCR analysis, we evaluated the expression profiles from a large panel of genes in TB patients and healthy individuals in an Indian cohort. Classification models were built and validated for their capacity to discriminate samples from TB patients and controls within this cohort and on external independent gene expression datasets. A combination of only four genes distinguished TB patients from healthy individuals in both cross‐validations and on separate validation datasets with very high accuracy. An external validation on two distinct cohorts using a real‐time PCR setting confirmed the predictive power of this 4‐gene tool reaching sensitivity scores of 88% with a specificity of around 75%. Moreover, this gene signature demonstrated good classification power in HIV + populations and also between TB and several other pulmonary diseases. Here we present proof of concept that our 4‐gene signature and the top classifier genes from our models provide excellent candidates for the development of molecular point‐of‐care TB diagnosis in endemic areas. Synopsis: The ongoing tuberculosis pandemic stresses the urgent need for new tools to better control the global disease burden. A simple molecular test could provide a rapid point‐of‐care diagnostic tool to help reduce tuberculosis incidence rate in endemic areas. A small set of 4 genes provided excellent classification performance between tuberculosis patients and healthy individuals in an easily implemented RT–PCR setup. High classification power was observed in multiple cohorts from different geographical regions and ethnicities and was maintained in HIV + populations. The 4‐gene signature also distinguished tuberculosis from several other pulmonary diseases. Abstract : The ongoing tuberculosis pandemic stresses the urgent need for new tools to better control the global disease burden. A simple molecular test could provide a rapid point‐of‐care diagnostic tool to help reduce tuberculosis incidence rate in endemic areas.